2021
DOI: 10.1186/s12877-021-02136-7
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stress and depressive symptoms not neuropsychiatric symptoms predict caregiver burden in Alzheimer’s disease: a cross-sectional study

Abstract: Background Caregiver burden affects the caregiver’s health and is related to the quality of care received by patients. This study aimed to determine the extent to which caregivers feel burdened when caring for patients with Alzheimer’s Disease (AD) and to investigate the predictors for caregiving burden. Methods A cross-sectional study was conducted. One hundred two caregivers of patients with AD at Maharaj Nakorn Chiang Mai Hospital, a tertiary ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 48 publications
1
26
1
Order By: Relevance
“…So, female caregivers face the risk to perceive an especially higher burden. Contrary to our results, the Pinyopornpanish et al (39) study showed that no sociodemographic variables were significantly related to CB and NPI.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…So, female caregivers face the risk to perceive an especially higher burden. Contrary to our results, the Pinyopornpanish et al (39) study showed that no sociodemographic variables were significantly related to CB and NPI.…”
Section: Discussioncontrasting
confidence: 99%
“…Also, in the study by Chen et al, the results showed that NPI score was independently associated with mean NPI-burden score (38). Pinyopornpanish et al (39) study in 2021 also showed that the higher the NPS score, the higher the care pressure. In addition, among neuropsychiatric symptoms, hallucination (P = 0.010), AMD (P = 0.011), delusion (P = 0.003), depression (P = 0.001), and changes in appetite/eating (P = 0.013) had significant association with CB.…”
Section: Discussionmentioning
confidence: 92%
“…A prior study demonstrated that the overall Neuropsychiatric Inventory Questionnaires (NPI-Q) score, an instrument used for assessing BPSD, is associated with caregiver burden through caregiver stress and depression 18 . However, inconsistent results about the association between specific symptoms of BPSD and psychosocial outcomes in caregivers have been found among studies 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some behavioral symptoms may impact caregiver wellbeing more so than others and thus effects their reporting of frequency and severity. There is some evidence to suggest that the number of behaviors being managed versus behavior-type and perceived stress are associated with caregiver burden and depression [ 41 43 ]. The evidence is inconclusive and associational, lacking hypothesis-driven analyses or testing of causal mechanisms.…”
Section: Discussionmentioning
confidence: 99%